Human talar ontogeny: Insights from morphological and trabecular changes during postnatal growth. Issue 2 (6th August 2022) - Figus, Carla; Stephens, Nicholas B.; Sorrentino, Rita; Bortolini, Eugenio; Arrighi, Simona; Lugli, Federico; Marciani, Giulia; Oxilia, Gregorio; Romandini, Matteo; Silvestrini, Sara; Baruffaldi, Fabio; Belcastro, Maria Giovanna; et al.
Abstract: Objectives: The study of the development of human bipedalism can provide a unique perspective on the evolution of morphology and behavior across species. To generate new knowledge of these mechanisms, we analyze changes in both internal and external morphology of the growing human talus in a sample of modern human juveniles using an innovative approach. Materials and Methods: The sample consists of high‐resolution microCT scans of 70 modern juvenile tali, aged between 8 postnatal weeks and 10 years old, from a broad chronological range from Middle/Late Neolithic, that is, between 4800 and 4500 BCE, to the 20th century. We applied geometric morphometric and whole‐bone trabecular analysis (bone volume fraction, degree of anisotropy, trabecular number, thickness, and spacing) to all specimens to identify changes in the external and internal morphology during growth. Morphometric maps were also generated. Results: During the first year of life, the talus has an immature and globular shape, with a dense, compact, and rather isotropic trabecular architecture, with numerous trabeculae packed closely together. This pattern changes while children acquire a more mature gait, and the talus tends to have a lower bone volume fraction, a higher anisotropy, and a more mature shape. Discussion: The changes in talar internal and external morphologies reflect the different loading patterns experienced during growth, gradually shifting from an "unspecialized" morphology to a more complex one, following the development of bipedal gait. Our research shows that talar plasticity, even though genetically driven, may show mechanical influences and contribute to tracking the main locomotor milestones.